Determination of Virus Diseases in Lettuce Production Areas of Ankara, Eskisehir, and Konya Provinces of Turkey - Birol AKBAŞ; Ali Ferhan MORCA; Sevgi COŞKAN (Yüzüncü Yıl Üniversitesi Tarim Bilimleri Dergisi)
Winter vegetable cultivation is realized in several having suitable climate condition region of Turkey. Lettuce, an important winter crop for Turkey is cultivated in various provinces of the Central Anatolia Region. A lot of virus agents affect lettuce plants in the sense of quality and quantity. To identify these viral agents, surveys were conducted in lettuce cultivation areas in Ankara, Eskisehir and Konya provinces and 164 samples were collected during the vegetation period of 2017 and 2018. Collected samples were tested serologically by DAS-ELISA tests using specific commercial antibodies against the following viruses: Beet western yellows virus (BWYV), Broad bean wilt virus (BBWV), Cauliflower mosaic virus (CaMV), Cucumber mosaic virus (CMV), Lettuce mosaic virus (LMV), Mirafiori lettuce big-vein virus (MiLBVV), Radish mosaic virus (RaMV), Tobacco mosaic virus (TMV), Tobacco necrosis virus (TNV), Tobacco rattle virus (TRV), Tobacco streak virus (TSV), Tomato black ring virus (TBRV), Tomato spotted wilt virus (TSWV), Turnip mosaic virus (TuMV). Samples were also molecularly analysed by RT-PCR against 2 viruses [Lettuce big-vein associated virus (LBVaV) and Tomato infectious chlorosis virus (TICV)] that have no commercial serological kits. Additionally, MiLBVV that was serologically detected at a high rate in the region, was also confirmed by RT-PCR analysis in the study. As a result of the analysis, infection rates of LBVaV, MiLBVV, LMV, and TNV were found as 31.7, 19.5, 7.3 and 3.7 %, respectively. With the present study, LBVaV and MiLBVV were determined to be the most prevalent viruses in lettuce in the region.